1999
DOI: 10.1128/jb.181.8.2572-2583.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Mobilization and Leading Regions of the IncN plasmids pKM101 and pCU1

Abstract: The conjugative IncN plasmids pKM101 and pCU1 have previously been shown to contain identical oriT sequences as well as conserved restriction endonuclease cleavage patterns within theirtra regions. Complementation analysis and sequence data presented here indicate that these two plasmids encode essentially identical conjugal DNA-processing proteins. This region contains three genes, traI, traJ, and traK, transcribed in the same orientation from a promoter that probably lies within or near the conjugal transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 71 publications
(86 reference statements)
0
25
0
Order By: Relevance
“…S1). A donor carrying mini-pKM101 pRP100 mobilized transfer of pJG142, a plasmid that carries the entire traK/traJ/ traI/oriT mobilization (mob) region from pKM101 (Paterson et al, 1999), at frequencies slightly higher than observed for pKM101 in both solid surface and liquid matings (Fig. 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…S1). A donor carrying mini-pKM101 pRP100 mobilized transfer of pJG142, a plasmid that carries the entire traK/traJ/ traI/oriT mobilization (mob) region from pKM101 (Paterson et al, 1999), at frequencies slightly higher than observed for pKM101 in both solid surface and liquid matings (Fig. 1).…”
Section: Resultsmentioning
confidence: 98%
“…coli pKM101 is widely known for its mutagenic and protective properties in cells exposed to UV irradiation and other DNA-damaging agents (Ames et al, 1975). pKM101 also encodes a highly-efficient T4SS (Winans and Walker, 1985;Paterson et al, 1999). In this study, we capitalized on the construction of a pKM101 aeruginosa PAO1.…”
Section: Discussionmentioning
confidence: 99%
“…We then compared the genetic background of pC5 with that of seven publicly available plasmid sequences with high similarity (coverage, Ͼ90%; identity, Ͼ99%), all of which were identified in E. coli strains in European countries (20,21,22,23) (Table 1). They all maintained a typical IncN plasmid backbone scaffold, including a replicon and genes involved in plasmid stability, mutagenesis enhancement, antirestriction functions, and conjugative transfer (24). The difference among these plasmids was in the mosaic region that carried resistance genes and in the mobile genetic elements represented (Fig.…”
Section: Identification Of An Incn-type Plasmid Carrying Bla Ctx-m-1 mentioning
confidence: 99%
“…A classical example is the primase gene sog of REP I1 -MOB P12 plasmids, which is only partially required for conjugation between Escherichia coli cells (Chatfield et al, 1982), but is required to expand the recipient host range to Salmonella and other enterobacteria (Lanka & Barth, 1981). Mutations in genes stbABC located in the leading region of REP N -MOB F11 plasmid pKM101 decreased plasmid stability (Paterson et al, 1999). Homologs of gene ardA are present in the leading region of REP N -MOB F11 , REP Frep -MOB F12 and (Gotz et al, 1996); N (Carattoli et al, 2005) oxa2, aadA1, sul1, tetAR, asrABCDR S. Typhimurium (E, P, V, A) pWWO 116 580…”
Section: Establishment Modulementioning
confidence: 99%